2022
DOI: 10.1021/acs.joc.2c01507
|View full text |Cite
|
Sign up to set email alerts
|

Connect Four: Tetraarylated Dihydropentalenes and Triarylated Monocyclic Pentafulvenes from Cyclopentadienes and Enones

Abstract: In search of novel pentalenide ligands for use in organometallic chemistry and homogeneous catalysis, we report the scope of a straightforward base-promoted Michael annulation of cyclopentadienes with α,β-unsaturated ketones that allows the introduction of symmetrical as well as unsymmetrical aryl and alkyl substitution patterns including electron-donating as well as electron-withdrawing substituents. More than 16 examples of various isomers of 1,3,4,6-tetraarylated dihydropentalenes have been synthesized in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…We have recently described the facile and modular syntheses of tetra-substituted dihydropentalenes 59 and introduced the first tetra-arylated pentalenide, M 2 [Ph 4 Pn] (M = Li, Na, K) 60 and the first alkaline earth pentalenide, Mg[Ph 4 Pn] . 61,62 The increased solubility and ease of separation of MgX 2 transmetalation by-products (through induced precipitation by addition of 1,4-dioxane 63,64 ) are key advantages of Mg[Ph 4 Pn] over M 2 [Ph 4 Pn] which make it a prime candidate to explore the coordination chemistry of Ph 4 Pn 2− by way of salt metathesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently described the facile and modular syntheses of tetra-substituted dihydropentalenes 59 and introduced the first tetra-arylated pentalenide, M 2 [Ph 4 Pn] (M = Li, Na, K) 60 and the first alkaline earth pentalenide, Mg[Ph 4 Pn] . 61,62 The increased solubility and ease of separation of MgX 2 transmetalation by-products (through induced precipitation by addition of 1,4-dioxane 63,64 ) are key advantages of Mg[Ph 4 Pn] over M 2 [Ph 4 Pn] which make it a prime candidate to explore the coordination chemistry of Ph 4 Pn 2− by way of salt metathesis.…”
Section: Introductionmentioning
confidence: 99%
“…[55][56][57] However, auxiliary ligand exchange reactions of late d-block pentalenide complexes are unknown save for Manriquez and co-workers who reported that [Cp*Ru II (μ:η 5 :η 3 Pn)Rh I (COD)] will liberate COD to form [Cp*Ru II (μ:η 5 :η 3 Pn)Rh I (CO) 2 ] when exposed to a CO atmosphere. 58 We have recently described the facile and modular syntheses of tetra-substituted dihydropentalenes 59 and introduced the first tetra-arylated pentalenide, M 2 [Ph 4 Pn] (M = Li, Na, K) 60 and the first alkaline earth pentalenide, Mg[Ph 4 Pn]. 61,62 The increased solubility and ease of separation of MgX 2 transmetalation by-products (through induced precipitation by addition of 1,4-dioxane 63,64 ) are key advantages of Mg[Ph 4 Pn] over M 2 [Ph 4 Pn] which make it a prime candidate to explore the coordination chemistry of Ph 4 Pn 2− by way of salt metathesis.…”
Section: Introductionmentioning
confidence: 99%
“…§ Remarks regarding the access of multisubstituted dihydropentalenes can be found in the corresponding literature. 8,22 https://doi.org/10.26434/chemrxiv-2023-z8jdq ORCID: https://orcid.org/0000-0002-7613-1838 Content not peer-reviewed by ChemRxiv. License: CC BY 4.0 4 Scheme 1: Substituted pentalenides reported to date (left) and contribution of the work reported here (right).…”
Section: Introductionmentioning
confidence: 99%
“…License: CC BY 4.0 dihydropentalenes with LiNEt2 in tetrahydrofuran (Scheme 2). 22 Indeed, their much improved solubilities allowed for full characterisation by multi-nuclear NMR spectroscopy as well as mass spectrometry. As was the case for 2, the 1 H and 13 C NMR spectra of 3 and 4 indicated D2h symmetry, and their 7 Li NMR chemical shifts between 0.7 and −3.8 ppm suggested solvent-separated ion pairs (SSIP) 23 in THF solution at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…One method involves the introduction of an exomethylene moiety to already existing cyclopentadienes. This is the conventional method, which involves condensation of aldehydes or ketones with cyclopentadienes in the presence of bases. The other method involves constructing fulvene rings from acyclic starting materials, that is, transition-metal-catalyzed cyclizations for the synthesis of fulvene rings from haloalkenes with alkynes or alkynyl esters with silyl acetylenes . Most of the above-mentioned reactions gave fulvenes bearing the same substituents, and the fulvenes lack diversity in substitution patterns and types of substituents.…”
mentioning
confidence: 99%